2016 IEEE Wireless Health (WH) 2016
DOI: 10.1109/wh.2016.7764552
|View full text |Cite
|
Sign up to set email alerts
|

Detecting change in depressive symptoms from daily wellbeing questions, personality, and activity

Abstract: Abstract-Depression is the most common mental disorder and is negatively impactful to individuals and their social networks. Passive sensing of behavior via smartphones may help detect changes in depressive symptoms, which could be useful for tracking and understanding disorders. Here we look at a passive way to detect changes in depressive symptoms from data collected by users' smartphones. In particular, we take two modeling approaches to understand what features of physical activity, sleep, and user emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
1
9
0
1
Order By: Relevance
“…Self-reported measures of sleep quality have been shown to be associated with state anxiety [59], anxiety disorders [60], and depression [61,62]. Sleep duration has been measured objectively in mobile sensing studies and shown to have a significant association with the severity of depressive symptoms [10,23,37]. although sleep duration and sleep disturbance features are different measures and as such cannot be directly compared, these studies support our results in demonstrating a general association between sleep and depression.…”
Section: Comparison With Other Studiessupporting
confidence: 82%
See 1 more Smart Citation
“…Self-reported measures of sleep quality have been shown to be associated with state anxiety [59], anxiety disorders [60], and depression [61,62]. Sleep duration has been measured objectively in mobile sensing studies and shown to have a significant association with the severity of depressive symptoms [10,23,37]. although sleep duration and sleep disturbance features are different measures and as such cannot be directly compared, these studies support our results in demonstrating a general association between sleep and depression.…”
Section: Comparison With Other Studiessupporting
confidence: 82%
“…Although we will provide a focused review of relevant works that have used audio data to predict or measure mood and anxiety disorders, there is a wealth of research that has looked at using many different data sources to investigate, predict, or measure the severity of many characteristics of health and mental health disorders. Interested readers are directed to work that has investigated subjects' general mood and mental health [9][10][11][12][13][14][15], substance abuse [16,17], depression [18][19][20][21][22][23][24], bipolar disorder [25][26][27][28][29], anxiety disorders [30][31][32], and schizophrenia [33,34]. The most commonly used sources of passively collected smartphone data in these works include subjects' geolocation (ie, GPS data), screen activity and phone usage time, SMS and phone metadata, and physical activity and motion sensor data.…”
Section: Previous Workmentioning
confidence: 99%
“…Some of these features are quite creative and worth mentioning. The most promising results for the nonclinical samples include the time spent in break rooms (ρ=−0.21, nonsignificant) [16], and less SD of stillness amount, which can be interpreted as a more uniform activity pattern (beta=−3.3, P <.001) [46]. For the clinical samples, it includes the increased amount of time with no sound detection ( speech pauses ; beta=0.34, P =.004) [55], increased number of calls missed (beta=0.05, P =.006) [6], and fewer incidences of quick or sudden movements ( jerk ; t =4.06, P <.001).…”
Section: Resultsmentioning
confidence: 99%
“…Self-reported measures of sleep quality have been shown to be associated with state anxiety [ 59 ], anxiety disorders [ 60 ], and depression [ 61 , 62 ]. Sleep duration has been measured objectively in mobile sensing studies and shown to have a significant association with the severity of depressive symptoms [ 10 , 23 , 37 ]. although sleep duration and sleep disturbance features are different measures and as such cannot be directly compared, these studies support our results in demonstrating a general association between sleep and depression.…”
Section: Discussionmentioning
confidence: 99%